Potential denitrification stimulated by water-soluble organic carbon from plant residues during initial decomposition - Surey, Ronny; Schimpf, Corinna M.; Sauheitl, Leopold; Mueller, Carsten W.; Rummel, Pauline S.; Dittert, Klaus; Kaiser, Klaus; Böttcher, Jürgen; Mikutta, Robert (Soil biology & biochemistry, 2020)
Denitrification usually takes place under anoxic conditions and over short periods of time, and depends on readily available nitrate and carbon sources. Variations in CO2 and N2O emissions associated with plant residues have mainly been explained by differences in their decomposability. A factor rarely considered so far is water-extractable organic matter (WEOM) released to the soil during residue decomposition. Here, we examined the potential effect of plant residues on denitrification with special emphasis on WEOM. A range of fresh and leached plant residues was characterized by elemental analyses, 13C-NMR spectroscopy, and extraction with ultrapure water. The obtained solutions were analyzed for the concentrations of organic carbon (OC) and organic nitrogen (ON), and by UV-VIS spectroscopy. To test the potential denitrification induced by plant residues or three different OM solutions, these carbon sources were added to soil suspensions and incubated for 24 h at 20 °C in the dark under anoxic conditions; KNO3 was added to ensure unlimited nitrate supply. Evolving N2O and CO2 were analyzed by gas chromatography, and acetylene inhibition was used to determine denitrification and its product ratio. The production of all gases, as well as the molar (N2O + N2)–N/CO2–C ratio, was directly related to the water-extractable OC (WEOC) content of the plant residues, and the WEOC increased with carboxylic/carbonyl C and decreasing OC/ON ratio of the plant residues. Incubation of OM solutions revealed that the molar (N2O + N2)–N/CO2–C ratio and share of N2O are influenced by the WEOM's chemical composition. In conclusion, our results emphasize the potential of WEOM in largely undecomposed plant residues to support short-term denitrification activity in a typical ˈhot spot–hot momentˈ situation. •Potential denitrification is closely related to water-soluble OC in plant residues.•Amount of water-soluble OC depends on the residue's chemical composition.•Chemical composition of water-soluble OM controls the molar (N2O + N2)–N/CO2–C ratio.